Institution of a Surgical Curriculum for Trabecular Microbypass Stent Placement - Hakim, Farida Esaa; Malhotra, Varun; Colby, Kathryn A.; Riaz, Kamran M. (Journal of Academic Ophthalmology, 2018)
Purpose This article evaluates whether a targeted, stepwise curriculum for microbypass stent placement leads to successful insertion of the iStent (Glaukos, Laguna Hills, CA) by resident surgeons.Participants Senior (postgraduate year 4) ophthalmology residents (9 residents) from three classes during the 2015 to 2016, 2016 to 2017, and 2017 to 2018 academic years.Design Residents participated in a three-stage surgical curriculum. First, a wet laboratory was held for residents to gain familiarity with the device and develop bimanual surgical proficiency. The wet laboratory involved several stations, with each station requiring increased dexterity for successful completion. Next, residents practiced bimanual intraoperative gonioscopy after routine phacoemulsification procedures. Finally, residents performed combined phacoemulsification and iStent insertion under the supervision of an experienced attending surgeon. Primary success was determined by correct anatomical placement of the device confirmed via subsequent intraoperative gonioscopy by the supervising surgeon. Secondary success was measured by change in intraocular pressure (IOP) and number of topical hypotensive medications used after surgery. Residents provided feedback about the effectiveness of the curriculum via an online survey.Results There were a total of 43 cases. There were no significant intraoperative complications, including hyphema. The iStent location was confirmed during both intraoperative and postoperative gonioscopy and was noted to be in appropriate position for the duration of the follow-up period (6–12 months) for all patients. Average preoperative IOP in our subjects was 17.5 ± 4.0 mm Hg and mean number of preoperative medications was 1.4 ± 1.0. At 6 months' postoperative, average IOP was 14.5 ± 2.2 mm Hg (13% reduction from baseline [±15%]). At 12 months' postoperative, average IOP was 14.4 ± 3.5 mm Hg, with a reduction of 14% (±18%). The mean number of medications at follow-up was 1.2 ± 1.1. Mean postoperative IOP at 6 and 12 months was significantly lower compared with baseline (p = 0.0002, p = 0.0001). Residents agreed that the curriculum prepared them to perform iStent insertion during residency and most residents felt prepared after residency.Conclusion This stepwise surgical curriculum for trabecular microbypass stent placement leads to successful performance of the procedure by residents and is a useful model for other residency programs.
Keywords: trabecular microbypass stent; graduate medical education; surgical education; ophthalmology education; surgical curriculum; resident outcomes